The Influence Of Brand Image And Social Media Marketing On Consumer Satisfaction Mediated By Purchase Decisions On Tiktok Shop - Situmorang, Maria Ernita; Helmi, Sulaiman; Roni, Mukran; Agustian, Wiwin (Indonesian Scientific Publication, 2024)
This research aims to determine the influence of Brand Image and Social Media Marketing on consumer satisfaction, with purchasing decisions as a mediating variable, on the TikTok Shop platform, the sample of this research is 100 active Tiktok Shop users, the method used is a quantitative method with Structural Equation Modeling analysis techniques (SEM) SmartPLS, the data used is primary and secondary data. The research results show that brand image has a positive and significant influence on consumer satisfaction, social media marketing has no and insignificant influence on consumer satisfaction, brand image has a positive and significant influence on consumer satisfaction mediated by purchasing decisions, social media marketing has a positive and significant influence on consumer satisfaction mediated by purchasing decisions